Effectiveness of a Psychological Program to Reduce Social Media Addiction Among High School Students - Sadeeq, Shaveen Hussein; Omar, Jehan Hussein (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2025)
Social media addiction is a growing concern among adolescents worldwide, with potentially serious impacts on psychological health, academic performance, and social relationships. This study aimed to evaluate the effectiveness of a psychological program designed to reduce social media addiction among tenth-grade students in Duhok Governorate, Kurdistan Region of Iraq. The study employed a quasi-experimental design with pre-test and post-test measurements. The sample consisted of 23 tenth-grade students (aged 15 years and above) who exhibited high levels of social media addiction according to a validated scale. The intervention was a 12-session psychological program based on cognitive-behavioral approaches, delivered twice weekly for 45 minutes per session. The program incorporated techniques such as self-control training, rational thinking skills, time management, relaxation exercises, and positive reinforcement strategies. Data were collected using the Social Media Addiction Scale (Younis, 2016) and analyzed using t-tests and Cohen's effect size calculations. Findings revealed that participants had high levels of social media addiction at baseline (M=64.52, SD=5.17), significantly higher than the hypothetical mean (t=4.18, p<0.05). Following the intervention, there was a statistically significant decrease in addiction levels (M=53.43, SD=10.13; t=5.24, p<0.05), with a large effect size (Cohen's d=1.09). The results indicate that the psychological program was effective in reducing social media addiction among the participants. The study demonstrates that structured psychological interventions based on cognitive and behavioral approaches can effectively reduce social media addiction among adolescents. The findings suggest that implementing similar programs in educational settings could be beneficial in addressing the growing problem of social media addiction among students, particularly in regions where digital literacy education and awareness about risks of excessive social media use are limited